Long wavy copper stretchable interconnects fabricated by continuous microcorrugation process for wearable applications. Issue 3 (9th March 2020) - Yamamoto, Michitaka; Karasawa, Ryu; Okuda, Shinji; Takamatsu, Seiichi; Itoh, Toshihiro
Abstract: Continuous microcorrugation processes have been developed to form long vertical wavy structures of copper (Cu) foil electrodes for the development of long stretchable interconnects of wearable devices and electronic textiles. Vertical wavy stretchable interconnects in previous studies suffer from low uniformity and limited size due to their wrinkling process with prestretched rubber substrate. Therefore, we propose a continuous metal foil forming process where a long flat Cu foil is continuously deformed into a wavy shape between two three‐dimensional printed gears. 5‐μm Cu foils were corrugated into a wavy structure with waves having 620‐μm pitch and 270‐μm height by the microcorrugation process. The fabricated wavy Cu interconnects showed a 40% stretchability. After microcorrugation, the interconnects were embedded in silicone rubber to protect them from mechanical scratch and improve their elasticity. The interconnects exhibited a 60% stretchability. Finally, a 25 cm‐long stretchable light emitting diodes (LEDs) ribbon with a stretchability over 20% was demonstrated by connecting the LEDs with our wavy Cu interconnects for electronic textile applications. The results demonstrate the effectiveness of our microcorrugation process in the fabrication of long uniform vertical interconnects. Abstract : Microcorrugation processes have been developed to form vertical wavy structures of Cu foil electrodes for stretchable interconnects. Continuous metal foil forming process where a flat Cu foil is continuously deformed into a wavy shape between two 3D‐printed gears was proposed. Microcorrugation process succeeded to form 5‐μm Cu foils into a wavy structure with waves having 620‐μm pitch and 270‐μm height. The microcorrugate Cu foil showed a 40% stretchability.